Reflexões do ensino de química: o que dizem os alunos atendidos pelo centro de apoio ao deficiente visual em Mossoró/RN. - Batista, Maria José Rufino (Universidade Federal Rural do Semi-Árido, 2021)
This work aims to analyze the teaching of chemistry from the perspective of students served by CADV of Mossoró/RN, in addition to knowing the methodologies in chemistry classes, and whether they are making the learning of these students. In the methodological path, bibliographic research and field research were used with the application of interviews with open questions, with the braille teacher, with the chemistry teacher and with four students attended by CADV in Mossoró/RN, in order to understand how the chemistry classes are going and what methodologies are being applied. As a result, it was identified that CADV promotes a good inclusion work with different activities, however there are some weaknesses in the scope of teaching chemistry. It was noticed that there is no teacher trained in the area, that there is no interaction between Braille and chemistry and the methodologies are decontextualized, following the practice of reading the textbook. Access to content just by reading the textbook limits access to chemical knowledge and the autonomy of students with DV. Thus, it is considered necessary that those who propose to teach chemistry for DV know the reality of public schools and support centers for the visually impaired, as well as the real difficulties and needs for adapting didactic materials that promote meaningful learning.
Keywords: Deficiência visual; Ensino de química; Materiais didáticos; Visual impairment; Chemistry teaching; Teaching materials; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL